2009
DOI: 10.1097/sla.0b013e3181bce5bd
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Barrier Dysfunction in a Randomized Trial of a Specific Probiotic Composition in Acute Pancreatitis

Abstract: Bacteremia, infected necrosis, organ failure, and mortality were all associated with intestinal barrier dysfunction early in the course of acute pancreatitis. Overall, prophylaxis with this specific combination of probiotic strains reduced bacterial translocation, but was associated with increased bacterial translocation and enterocyte damage in patients with organ failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(92 citation statements)
references
References 29 publications
(32 reference statements)
1
88
1
2
Order By: Relevance
“…In studies using the L/M ratio an effect was not found more often than studies using other sugar tests. However, in all studies using PEG no effect was observed [17,18,53]. Interestingly in one study effects of probiotic supplementation on plasma levels of LPS were observed, despite a lacking effect as measured with PEG [53].…”
Section: Measurement Of Intestinal Permeabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…In studies using the L/M ratio an effect was not found more often than studies using other sugar tests. However, in all studies using PEG no effect was observed [17,18,53]. Interestingly in one study effects of probiotic supplementation on plasma levels of LPS were observed, despite a lacking effect as measured with PEG [53].…”
Section: Measurement Of Intestinal Permeabilitymentioning
confidence: 97%
“…Other methods were PEG and in some studies tight junction protein staining was used. IFABP or IgA/IgG were additionally measured in some studies [17,18,50] as indirect indices of the epithelial barrier integrity. CRP, TNF-α, α1-antitrypsin, mesenteric lymph nodes biopsies and PCR were often used to assess inflammatory and/or bacterial activity or translocation.…”
Section: Measurement Of Intestinal Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although probiotics can decrease bacterial translocation in a healthy environment, paradoxically they may be associated with an increase in enterocyte damage and bacterial translocation in a patient with organ failure [65].…”
Section: Composition Of Enteral Nutritionmentioning
confidence: 99%
“…It is hypothesized that infection of pancreatic necrosis is mediated by bacterial translocation from the gut, provoked by disturbed intestinal motility, bacterial overgrowth, and increased mucosal permeability [15,16,17,18,19]. Nasoenteric tube feeding is believed to stimulate intestinal motility, which may reduce bacterial overgrowth and preserve gut mucosal integrity through the stimulation of splanchnic blood flow [20,21].…”
Section: Feeding In Pancreatitismentioning
confidence: 99%